Pendugaan Umur Simpan Tomat (Solanum lycopersicum L) Terolah Minimal menggunakan Metode ASLT (Accelerated Shelf Life Test) Model Arrhenius - Zahroh, Inarotul; Syska, Kavadya; Nurhayati, Asti Dewi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Minimal processing of tomatoes (Solanum lycopersicum L.) have become increasingly popular due to their ability to preserve nutritional content and organoleptic characteristics. The minimal processing method offers advantages in minimizing natural changes in the product; however, the main challenge lies in maintaining the quality and freshness of the product during storage. This research aims to determine the shelf life of minimally processed tomatoes using the ASLT method with the Arrhenius model and to identify quality changes that occur during storage of minimally processed tomatoes. The Accelerated Shelf Life Test (ASLT) method proves to be an effective approach for predicting the shelf life of a product rapidly. The Arrhenius model, detailing the relationship between temperature and the rate of chemical reactions, is employed to analyze the kinetics of reactions during accelerated storage. The combination of these two methods provides an accurate overview of the product's shelf life. In this research, minimally processed tomatoes were packaged using wrapping plastic, HDPE (High-density polyethylene), and PP (Polypropylene), then stored at temperatures of 10°C and 30°C. The research results indicate that the highest pH value at 10°C with the wrapping packaging treatment was 3.6, and at 30°C, the highest pH value with wrapping packaging was also 3.6. The highest weight loss of tomato fruit at 10°C was observed with the wrapping packaging treatment at 1.25%, and at 30°C, the highest weight loss was 1.55% with wrapping packaging. The highest total soluble solids value was 4.27% with wrapping packaging at 10°C, and at 30°C, the highest total soluble solids in tomato fruit was 4.1% with wrapping packaging. The estimated shelf life of minimally processed tomatoes obtained results for the longest shelf life was wrapping packaging with an estimated shelf life of 15 days at 10°C, while the shortest shelf life was 2 days at 30°C with HDPE packaging. These findings provide insights into the stability of minimally processed tomato products and lay the foundation for the development of optimal storage strategies. The application of ASLT with the Arrhenius model can assist the food processing industry in enhancing efficiency and product quality, particularly in the case of minimally processed tomato products.